Saxagliptin reduces the injury of Alzheimer’s disease cell model by down-regulating the expression of miR-483-5p: Saxagliptin mitigates Alzheimer’s model via miR-483-5p - Hou, Yiting; Dong, Lihua; Cao, Lihua (Cellular and Molecular Biology, 2023)
This study aimed to investigate the effect of saxagliptin on the injury of Alzheimer’s disease (AD) cell model and its possible mechanism. SK-N-SH cells were cultured in vitro and divided into CON group, AD group, AD+L-SAX group, AD+M-SAX group, AD+H-SAX group, AD+anti-miR-NC group, AD+anti-miR-483-5p group, AD+SAX+miR-NC group and AD+SAX+miR-483-5p group. Then the levels of MDA, SOD and GSH-Px in each group were detected by ELISA method; cell apoptosis was detected by flow cytometry; the protein expression levels of Bax and Bcl-2 were detected by Western Blot; the expression level of miR-483-5p was detected by RT-qPCR. Compared with the control group, MDA content, apoptosis rate, and the expression of Bax protein and miR-483-5p increased in the AD group (P<0.05), while the activity of SOD and GSH-Px and the expression of Bcl-2 protein decreased (P<0.05). Compared with the AD group, MDA content, apoptosis rate, and the expression of Bax protein and miR-483-5p decreased in the AD+L-SAX group, AD+M-SAX group and AD+H-SAX group (P<0.05), while the activity of SOD and GSH-Px and the expression of Bcl-2 protein increased (P<0.05). Compared with AD+anti-miR-NC group, MDA content, apoptosis rate, and the expression of Bax protein and miR-483-5p decreased in the AD+anti-miR-483-5p group (P<0.05), while the activity of SOD and GSH-Px and the expression of Bcl-2 protein increased (P<0.05). Compared with AD+SAX+miR-NC group, MDA content, apoptosis rate, and the expression of Bax protein and miR-483-5p increased in the AD+SAX+miR-483-5p group (P<0.05), while the activity of SOD and GSH-Px and the expression of Bcl-2 protein decreased (P<0.05). Saxagliptin may reduce the injury of Alzheimer’s disease cell model by down-regulating the expression of miR-483-5p.